Global, regional, national burden and trends of unintentional injuries from 1990 to 2021 and projections to 2035: a systematic analysis of the Global Burden of Disease study 2021 - Qin, Wenpeng; Liu, Xiugen; Nong, Jusen; Feng, Daqin; Liu, Guoshen; Xie, Jiaqi; Huang, Weicheng; Liang, Hao; Yan, Linlu; Tang, Haojun; Qin, Fengjun; Huang, Fei; et al. (Frontiers in Public Health, 2025)
BackgroundUnintentional injuries, including drowning, falls, and heat-related incidents, constitute a substantial challenge to global health. The present study utilizes data from t the Global Burden of Disease (GBD) database to investigate the burden of unintentional injuries spanning the period from 1990 to 2021. It integrates these findings with future projections and advanced analytical approaches.MethodsEpidemiological data pertaining to unintentional injuries, sourced from the Global Burden of Disease (GBD) database covering the period 1990–2021, were subjected to analysis. This study centered on three core indicators: age-standardised incidence rate (ASIR), age-standardised mortality rate (ASDR), and age-standardised disability-adjusted life years (DALYs). The data were stratified by geographical region and classified in accordance with the Sociodemographic Index (SDI). The analytical approaches employed encompassed the computation of key metrics, trend evaluation, determination of relative variations, as well as the application of sophisticated methodologies for frontier analysis and projections, with all analyses conducted using R software.ResultsFrom 1990 to 2021, the global number of new cases of unintentional injuries rose, while both mortality figures and DALYs cases associated with such injuries trended downward. Age-standardized rates for incidence, mortality, and DALYs also decreased to varying extents. Among level 3 classifications of unintentional injuries based on age-standardized rates, falls imposed the heaviest burden. A robust positive association was identified between ASIR and SDI, in contrast to the strong inverse correlations observed between SDI and both ASDR and age-standardized DALYs rate. Frontier analysis encompassing 204 countries and territories further indicated that age-standardized DALYs rates generally diminished as SDI levels climbed. Projections extending to 2035 suggest that the global downward trajectory will persist for age-standardized indicators, including ASIR, ASDR, and age-standardized DALYs rate.ConclusionAlthough ASIR of unintentional injuries decreased between 1990 and 2021, and the burden of such injuries is relatively lighter in regions with a high SDI, notable disparities remain across countries. Sustained scholarly inquiry and innovative healthcare policies are imperative to further alleviate the burden imposed by unintentional injuries.